2019
DOI: 10.1111/jphs.12289
|View full text |Cite
|
Sign up to set email alerts
|

Measuring knowledge and attitudes towards the utilization of pharmacogenetic testing among physicians

Abstract: Objective Pharmacogenetic (PGx) testing is a relatively new available diagnostic tool, which aims to prescribe tailored medications based on genetic differences. However, this innovation has been slowly adopted by physicians. This study aims to test Rogers's diffusion of innovation theory to assess knowledge and attitudes towards the use of PGx testing among physicians. Method A sample of community physicians in South Florida was invited to complete an online survey about PGx testing. Practicing physicians who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The major barriers in implementing pharmacogenomic testing in Australian hospitals, as identified in this study, centred on a lack of knowledge, inadequate guidance and HCP' low confidence in their ability to use and implement pharmacogenomic data in practice. These barriers have been identified previously in other countries 4–6,8,10,15,16,18 in both tertiary 2,9,14,17,20 and primary care 3,7,19,25,26 and align and expand on previous research conducted in Australia more than 7 years ago 17,18 …”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The major barriers in implementing pharmacogenomic testing in Australian hospitals, as identified in this study, centred on a lack of knowledge, inadequate guidance and HCP' low confidence in their ability to use and implement pharmacogenomic data in practice. These barriers have been identified previously in other countries 4–6,8,10,15,16,18 in both tertiary 2,9,14,17,20 and primary care 3,7,19,25,26 and align and expand on previous research conducted in Australia more than 7 years ago 17,18 …”
Section: Discussionsupporting
confidence: 85%
“…Other significant barriers were associated with the HCP' opportunity to test, which could be restricted by their practice environment, social context and available resources (COM-B Opportunity barrier). Reviews of Would not affect (1) Unsure (2) Would affect decision (3) Capability pharmacogenomic implementation studies have found that turnaround times of pharmacogenomic test results might be a challenge to implementation. 27,28 Where noted as a barrier, turnaround times were found to vary from 3 to 42 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations